A Comparative Study on MPA’s and OECM’s Conservation Management: Key Findings and Lesson Learned - MARIUS YOSEF SERAN; Septian Hutagalung; Kusnanto; Laurensius Sandrio; Roseven Rudiyanto (Jurnal Penelitian Terapan Mahasiswa, 2024)
Marine Protected Areas (MPAs) and Other Effective Area-Based Conservation Measures (OECMs) are two conservation approach models that offer conservation programs through activities related to protecting marine ecosystems and promoting social and economic sustainability issues. and culture. Even though they are two different approaches, they complement each other and have an important role in conservation activities. This study uses a comparative method to analyze the similarities and differences between MPAs and OECDMs. The research results show that these two approaches have the same main goal, namely protecting biodiversity and promoting sustainable ecosystems. Meanwhile, in relation to different aspects, there are several components such as definitions, approaches and implementation mechanisms. MPAs tend to be more focused on protecting specific areas with restrictions on human activity and activities, whereas OECMs offer greater flexibility by integrating conservation in a variety of land and resource use contexts. In terms of conservation objectives, both MPAs and OECDS aim to improve the quality of life of entire ecosystems, protect threatened species, and support local economic sustainability. This can be done through ecotourism and responsible resource management. Thus, the implementation of these two approaches can have a positive impact on all stakeholders involved in conservation and sustainable development.